Development of Discord Server Towards Blended Learning Model in 100 Meter Athletic Run Through Video Media in Class VII Students SMP Negeri 2 Rejang Lebong - Taqwim, Ahsani (Yayasan Sembilan Pemuda Indonesia, 2023)
This research aims to explore the development of a Discord server as a platform for implementing a blended learning model in the context of 100-meter athletic run training among Class VII students at SMP Negeri 2 Rejang Lebong. The research involved designing and implementing various learning activities on the Discord server, including video tutorials on athletic techniques, live streaming of expert demonstrations, interactive quizzes, and discussion forums for student collaboration and feedback. The server also served as a platform for teachers to provide timely guidance and personalized support to students. Data collection involved pre- and post-intervention assessments, as well as surveys and interviews to gather student feedback on their experiences with the Discord server. The results indicated a positive impact of the blended learning model on student engagement, motivation, and performance in the 100-meter athletic run. Students appreciated the flexibility and interactive nature of the online platform, which allowed them to review instructional videos at their own pace and seek clarifications from both peers and teachers. This research contributes to the growing body of literature on the effective integration of digital technologies in physical education, specifically in the context of 100-meter athletic run training. The findings highlight the potential of the Discord server as a versatile tool for creating a collaborative and interactive learning environment, fostering student-centered learning, and promoting physical activity engagement.